Forecasting long-term sediment yield from the upper North Fork Toutle River, Mount St. Helens, USA - Meadows, Tim (2014)
The Toutle-Cowlitz River system experienced dramatic landscape disturbance during the catastrophic eruption of Mount St Helens on May 18, 1980. The eruption was triggered by a 2.5 km3 debris avalanche which buried the upper 60 km2 of the North Fork Toutle River catchment to an average depth of 45 m and obliterated the surface drainage network. Subsequent channel response on the debris avalanche, dominated by incision and widening, has delivered significant quantities of sediment to downstream reaches where resultant deposition has reduced channel capacity and heightened flood risk. Estimates of future sediment yield from the upper North Fork Toutle River are therefore required to inform development of sustainable options for long-term flood risk mitigation. Previous estimates have been based on extrapolation of post-eruption trends in sediment yield and channel network evolution, but the divergent predictions reported in a number of studies have clouded effective decision-making regarding long-term sediment management. This study therefore uses a numerical, landscape evolution model (CAESAR-Lisflood) to make long-term forecasts of sediment yield based on process simulation rather than extrapolation. A suite of forecasts of cumulative catchment sediment yields up to 2100 are produced using scenario-based model runs designed to account for uncertainty associated with the hydrological impacts of climate change and the model coefficient for lateral mobility. The forecasts fall in a narrow band +/-20% of the mean that lies between two previous estimates derived from the extrapolation of post-eruption trends. Importantly, predicted trends in future annual sediment yield are predominantly linear, although some limited decay is evident for runs in which modelled channel lateral mobility is lower. Sustained sediment production in the upper North Fork Toutle River is found to result from persistent bank erosion and channel widening. These findings cast doubt on the applicability of negative exponential decay functions based on the rate law to characterise post-disturbance sediment yield when lateral rather than vertical adjustments dominate channel evolution. Moreover, forecast trends in future sediment yield suggest that it may not be possible to manage future sediment-related flood risk along the lower Cowlitz solely by retaining sediment in the upper North Fork Toutle River catchment.